Технологія холодного соусу для здорового харчування з пектиновмісною сировиною - Чайка, О. В.; Куниця, Катерина Вікторівна (Видавничий дім "Гельветика", 2019)
Виконано комплексні дослідження, що дозволили теоретично і експериментально обґрунтувати ефективність і доцільність застосування пектину в якості фізіологічного функціонального інгредієнта при створенні майонезу. Обґрунтовано доцільність і ефективність застосування суміші дезодорованих рафінованої олії в співвідношенні: соняшникова: рапсова: соєва = 50,5%: 25%: 24,5%, що має збалансований склад ω-3: ω-6 жирних кислот, рекомендований для здорового харчування. Отримано і вивчені органолептичні і фізико-хімічні характеристики пектинів з яблучних і цитрусових, бурякового жому. Розроблено рецептуру майонезу для здорового харчування, що має збалансований жирнокислотний склад жирової фази в кількості 55% і 35% від маси емульсії відповідно, збагачений фізіологічно функціональними інгредієнтами: яблучним пектином і лактатом кальцію.

Comprehensive studies have been performed, which theoretically and experimentally substantiate the effectiveness and feasibility of using pectin as a physiologically and technologically functional ingredient in the creation of mayonnaise. The expediency and effectiveness of using a mixture of deodorized refied vegetable oils in the ratio: sunflwer: rapeseed: soybean = 50.5%: 25%: 24.5%, having a balanced composition of ω-3: ω-6 fatty acids, recommended for healthy eating, is justifid. The organoleptic and physicochemical characteristics of pectins from apple and citrus squeezes, beet pulp and pumpkin peels were obtained and studied. Such traditional emulsifirs as egg powder and milk powder were replaced with soya lecithin and it was found that in order to obtain a stable emulsion of the direct type containing 55% and 35% of the oil phase, 1.75% and 1.5% of soya lecithin should be introduced into the emulsion, respectively. It was revealed that to create a stable emulsion, the ratio of 1.0% soya lecithin and 1.5% apple pectin for mayonnaise is necessary. The introduction of apple pectin in the recipe helps to reduce the amount of soya lecithin in the recipe and to achieve the necessary rheological properties of the product. Technological conditions for the production of mayonnaise with apple pectin have been developed. As a result of the analysis of the dynamics of changes in the peroxide number and organoleptic characteristics during aging products, it was found that the duration of storage of mayonnaise with a mass fraction of fat 55% at a temperature of 18°C should not exceed 25 days. The energy value of the developed products is lower in comparison with the control samples at 22 kcal / g for mayonnaise, and the food value is much higher. The introduction of the developed recipes of mayonnaise with apple pectin into production will allow: expand the assortment of mayonnaise for a healthy diet; reduce nutritional defiiencies in polyunsaturated fatty acids, dietary fier and calcium; increase the demand for mayonnaise due to the improved consumer characteristics of these products.
Technology of cold sauce for healthy nutrition with pectine content
Keywords: майонез; пектин; харчування; рослинна олія; купажування олій; mayonnaise; pectin; food; vegetable oil; blending of oils